P-OGC53 Dashboarding for real-time analysis of oesophagogastric outcomes data. (16th December 2021) - Ash, Stephen; Antonowicz, Stefan; Matarangolo, Antonio; Menon, Nainika; Owen, Richard; Gillies, Richard; Sgromo, Bruno; Marshall, Robert; Maynard, Nick
Abstract: Background: The typical paradigm for surgical service evaluation is intermittent audit based on perceived clinical need and mandated requirements. A better model would be monitoring patient outcomes automatically in real-time, with up-to-date cumulative frequencies of key surgical performance indicators such as surgical quality and morbidity, as changes in performance could be detected and reacted to at an earlier stage. This study aimed to develop a dashboarding technology to support real-time visualisation of prospectively maintained oesophagogastric cancer surgery data. Methods: CODA is a bespoke databank (implemented in MS SQL Server, with HTML, C# and JavaScript) for oesophagogastric cancer care at our centre. We built on a custom dashboard interface for displaying this information in real-time, using Shiny for R and Tableau. We identified the key performance indicators (KPIs) to monitor in the dashboard, and defined benchmarks based on accepted standards, or our prevailing performance (based on 448 consecutive patients who underwent oesophagectomy between 2015 – 2020). The domains selected were surgical quality, length of stay, early mortality, and priority complications. Complications were defined according to the Esophagectomy Complications Consensus Group. Results: For surgical quality, our benchmarks based on prevailing performance were (i) >90% >15 lymph node yield (ii) <2-5% longitudinal R1 (iii) <20-30% CRM R1. For length of stay, our benchmarks were (i) >33% meeting 8 day discharge target (ii) <15% missing target discharge without a medical complication (iii) <20% staying longer than two weeks. For 30 & 90 day mortality, our benchmarks were 2% and 4% respectively. For complications, two sets were identified: (i) common complications (occurring at > 2 / year, monitored 2-yearly) (ii) impactful complications (>1 / year, >1 week median additional stay, monitored 5-yearly) Conclusions: The CODA dashboard provides real-time appraisal of oesophagogastric cancer surgery practice, highlighting changes in performance and providing opportunity for early intervention. The platform can be used for personal, departmental or inter-institutional service evaluation. The KPIs will be extended to oesophagogastric cancer survival as the test set matures. The interface and wider benefits of CODA implementation are presented, together with the dissemination plan for use in other oesophagogastric centres.